2022
DOI: 10.1021/acs.inorgchem.1c03944
|View full text |Cite
|
Sign up to set email alerts
|

One-Step versus Two-Step Valence Tautomeric Transitions in Tetraoxolene-Bridged Dinuclear Cobalt Compounds

Abstract: The syntheses of valence tautomeric compounds with multistep transitions using new redox-active ligands are the long-term goal of the field of bistable materials. The redox-active tetraoxolene ligand, 2,7-di-tert-butylpyrene-4,5,9,10-tetraone (pyreneQ–Q), is now developed to synthesize a pair of dinuclear compounds {[CoL2]2(pyreneSq–Sq)}­[Co­(CO)4]2·xCH2Cl2·2C6H5CH3 (1, x = 2, L = 1,10-phenanthroline, phen; 2, x = 1.5, L = 2,2′-bipyridine, bpy). Variable-temperature magnetic susceptibilities and single-crystal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 103 publications
3
16
0
Order By: Relevance
“…We would like to note that the half-step SCO in systems with low cooperativity is somewhat unusual. In the more specific case of VT-SCO, such behavior is generally observed in dinuclear cobalt complexes. , The observation of the half-step VT-SCO behavior in mononuclear complexes 5 and 7 might stem from the subtle crystal packing effects, which lead to the formation of slightly different coordination geometry around the Co metal centers upon the loss of interstitial solvent. Unfortunately, the solvent loss leads to disintegration of the single crystals, which prevents investigation of this problem beyond the assumption described above.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…We would like to note that the half-step SCO in systems with low cooperativity is somewhat unusual. In the more specific case of VT-SCO, such behavior is generally observed in dinuclear cobalt complexes. , The observation of the half-step VT-SCO behavior in mononuclear complexes 5 and 7 might stem from the subtle crystal packing effects, which lead to the formation of slightly different coordination geometry around the Co metal centers upon the loss of interstitial solvent. Unfortunately, the solvent loss leads to disintegration of the single crystals, which prevents investigation of this problem beyond the assumption described above.…”
Section: Resultsmentioning
confidence: 95%
“…The identity and purity of the compounds were confirmed by SCXRD and elemental analysis, respectively, which showed the presence of interstitial solvent that was lost completely upon drying or partially substituted by water molecules absorbed from air. Infrared spectroscopy (Figure S1) revealed that all complexes exhibit the quinone CO (around 1600 cm –1 ) and semiquinone C–O (1430–1480 cm –1 ) stretching bands characteristic for Co VT complexes. TGA analysis showed that the complexes, in general, remained stable to 450 K (Figure S2).…”
Section: Resultsmentioning
confidence: 99%
“…To provide a guide prior to synthetic work and subsequent experimental studies, an initial survey of the electronic structures and the relative stability of 1 2+ (PF 6 ) 2 , 1 + (PF 6 ) , 1 , 2 , 3 , and 3 2 + (PF 6 ) 2 was carried out using density functional theory (DFT) calculations based on optimized gas-phase geometries (Tables S1–S3; Figures S1–S6). The electromer energies ( E , kcal mol –1 ) were calculated using the UTPSSh/6-311++G­(d,p) , DFT method (Table S4) with the inclusion of zero-point energy (ZPE) in Gaussian 16, a method that has previously been successful in the calculation of electromer energies for cobalt complexes with redox-active ligands. , It is important to note that factors such as lattice effects and solvent can complicate the straightforward translation of relative energies from calculations performed on isolated molecules in the gas phase to experimental systems.…”
Section: Resultsmentioning
confidence: 99%
“…Until now, considerable research and development of transition metal complexes is ongoing because of their tremendous applications and advances in the field of bioinorganic chemistry, medicinal chemistry, drug delivery, catalysis, gas sorption, sensing, and molecular magnetism. , These applications and advances have rekindled our interest in the synthesis and physicochemical characterization of different transition metal complexes. Among them, high-spin Co­(II) complexes are very popular to the coordination/material chemists owing to their interesting magnetic properties. They are good candidates that act as single-molecule magnets , and single-chain magnets , because of their half-integer spins ( S = 3 / 2 ) and sizable magnetic anisotropy arising from spin-orbit coupling among the ligand field states. Several studies on mono- and dinuclear Co­(II) complexes have shown the impact of coordination number, geometrical arrangement, and identity of the ligand on zero-field splitting parameters and magnetic relaxation rates. In this context, the dinuclear Co­(II) complexes bearing alkoxide/phenoxide/hydroxide bridges have attracted much attention in recent times. Particular interest has been focused on the relationship between their structures and magnetic properties in order to understand the detailed magneto-structural correlations. It should be mentioned that the dimetallic complexes constitute an emerging and sophisticated subgroup of compounds within the family of multinuclear metal assemblies. Therefore, the dinuclear cobalt­(II) complexes having well-established structures are suitable candidates for investigating the magnetic interactions between the paramagnetic metal centers transmitted via different endogenous and/or exogenous bridging ligands. , However, it is still a labyrinth because not all the structures could be constructed as predicted, which might be ascribed to the different factors that control the formation of their molecular architectures. , The main challenge of building well-defined dinuclear complexes with expected geometric and electronic structures lies in the assembly of nuclearities induced by several factors, such as ligand-to-metal ratio, nature of the exogenous ancillary bridging groups, coordinating/noncoordinating ions, solvent systems, pH, temperature, etc …”
Section: Introductionmentioning
confidence: 99%